Learning Management at a Mobilizing School in Ternate City - Sahmal, Jusman A.; Wijayanti, Wiwik (Journal of World Science, 2024)
The quality of education in Indonesia, particularly in 3T (Disadvantaged, Frontier, Outermost) areas, remains a significant challenge due to weak student literacy and numeracy skills, a problematic school climate, and ineffective learning management. This research aims to explore and describe the learning management practices implemented in driving schools (Sekolah Penggerak) in Ternate City. This study examines how learning management, based on the differentiated learning approach, can address these challenges and improve educational quality. This research adopts a descriptive qualitative method involving eight teachers and four principals from the first batch of driving schools. Data were collected through interviews, field observations, and document analysis. The results indicate that learning management involves three key stages: 1) Planning, which focuses on teacher preparedness and learning administration; 2) Implementation, where differentiated learning methods are applied; and 3) Evaluation, which employs formative and summative assessments. These practices contribute to enhanced learning quality, especially in under-resourced schools. The study concludes that differentiated learning and effective management practices can significantly improve educational outcomes in 3T areas.